A novel high efficiency and ultra-stable red emitting europium doped pyrophosphate phosphor for multifunctional applications. Issue 17 (22nd July 2021) - Wang, Chuang; Li, Ying; Chen, Shuanglong; Li, Yanyan; Lv, Qingyi; Shao, Bohuai; Zhu, Ge; Zhao, Lei
Abstract : The RBPO:Eu 3+  phosphor developed by the nonlinear optical material-inspired methodology can serve as a potential candidate in solid state lighting applications, artistic appreciation or some applications under extreme conditions. Abstract : The development of high quantum efficiency and stable red emitting phosphors with high color purity is an urgent need for multifunctional optical applications. In this work, we propose a nonlinear optical material (NLOM)-inspired methodology to synthesize a novel red emission pyrophosphate phosphor Rb2 Ba3 (P2 O7 )2 :Eu 3+ . XRD Rietveld refinement and energy dispersive X-ray spectroscopy were then exploited to obtain information on the phase purity, crystal structure and chemical composition. Moreover, the optical bandgap of different Eu 3+ doped Rb2 Ba3 (P2 O7 )2 phosphors was analyzed by diffuse reflectance spectroscopy and further confirmed by first principles calculation. Furthermore, the Eu 3+ site occupation preference, the characteristic luminescence properties and luminescence kinetics as a function of Eu 3+ doping concentration were investigated by employing the cryogenic spectra at 4 K, room temperature emission spectra and decay curves. The luminescence analysis indicated that Rb2 Ba3 (P2 O7 )2 :Eu 3+ could emit red emission light with high quantum efficiency (IQE ∼ 77.04%), high color purity (96.4%) and excellent thermal stability (87%@ 140 °C) under ultraviolet light excitation. In addition, the excellent stability of Rb2 Ba3 (P2 O7 )2 :Eu 3+ against external pressure, cathode-ray irradiation, water and acid–base was further proved by pressure-driven (from 0 to 20 GPa) luminescence analysis, cathodoluminescence analysis and emission photography after infiltrating in water, acid, and alkali. The current work indicates that Rb2 Ba3 (P2 O7 )2 :Eu 3+ exhibits unprecedented excellent luminescence properties compared to other recently discovered phosphate red phosphors, and can serve as a potential red phosphor candidate in multifunctional optical applications, like LEDs, FEDs, artistic appreciation or some applications under extreme conditions (high temperature, strong pressure, and infiltrating in water, acid, and alkali).